Choline in immunity: a key regulator of immune cell activation and function - Maia, Catarina; Fung, Chin Wai; Sanchez-Lopez, Elsa (Frontiers in Immunology, 2025)
Nutrient availability is a strong determinant of cell function. Immune cells, which must rapidly activate transcriptional, proteomic, and metabolic programs to fulfill their functional roles, depend on nutrient supply to generate the building blocks needed for the production of immune effectors. While glucose, glutamine, and amino acids are well-recognized as critical energy sources and carbon donors during immune activation, the contribution of choline, a vitamin-like metabolite, has been overlooked. Once taken up by cells, choline plays a vital role in several biological processes. It is a precursor for phosphatidylcholine, the primary phospholipid in cellular membranes, and is also essential for synthesizing the neurotransmitter acetylcholine. Additionally, when directed toward mitochondria and betaine synthesis, choline serves as a methyl donor for histone and protein methylation, key processes that regulate gene expression and cellular activity. In this review, we examine the latest research on how immune cells utilize and metabolize choline, as well as its broader implications for immune-related disorders and overall human health. We also discuss recent and ongoing clinical studies investigating the effects of choline supplementation and the potential use of choline-derived metabolites as biomarkers for therapy response.